Management of higher education: characteristic features of development in the period of digitalization and informatization of society - Кошербаева, Айгерим (Pedagogy and Psychology, 2022)
The article reveals innovative directions and new principles of management of the higher education system in the digital age. The author focuses on the main management tools – knowledge, innovation and ways of their practical application. Information based on knowledge becomes the most important, meaningful and accessible for all segments of the population, organizations, social groups and society as a whole. At the same time, up-to date information is an inexhaustible reserve for the development of mankind. Within the framework of the study, attention is focused on the development of various types of higher school management, as well as a content analysis of the strategy of Kazakh universities, the Abai National Pedagogical University. At the same time, the issues of personnel training and other modern challenges of social development are raised, the points of view of well-known management theorists and practitioners are given.